2018
DOI: 10.2135/cropsci2017.12.0748
|View full text |Cite
|
Sign up to set email alerts
|

Winter Hardiness and Freezing Tolerance in a Hairy Vetch Collection

Abstract: Hairy vetch (Vicia villosa Roth) is a winter‐annual legume that is grown as a cover crop and for forage. Although more winter tolerant than most leguminous winter annuals, it does not reliably overwinter in the upper Midwestern United States. Our objectives were to screen a collection of accessions for winter hardiness and develop a screening method for freezing tolerance in a controlled setting. We evaluated 30 accessions (commercial germplasm and breeding populations) in multiple Minnesota environments. Aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…As mentioned above, a lack of geographical signature in the pattern of population variation, as occurs with other allogamous species (Garayalde et al, 2011), can also be explained by human activities on seed dispersal and genetic drift (Knapp and Rice, 1998). Cultivated populations are openpollinated and highly heterogeneous and would be subject to natural selection and genetic drift throughout the cycles (Wiering et al, 2018). These results are consistent with observed in the phenotypic traits.…”
Section: Genotypic Variabilitysupporting
confidence: 81%
“…As mentioned above, a lack of geographical signature in the pattern of population variation, as occurs with other allogamous species (Garayalde et al, 2011), can also be explained by human activities on seed dispersal and genetic drift (Knapp and Rice, 1998). Cultivated populations are openpollinated and highly heterogeneous and would be subject to natural selection and genetic drift throughout the cycles (Wiering et al, 2018). These results are consistent with observed in the phenotypic traits.…”
Section: Genotypic Variabilitysupporting
confidence: 81%
“…Due to the outcrossing nature of most legume cover crop species, the genetic units available to breeders are typically populations with high genetic heterogeneity. Other studies with hairy vetch have also found greater trait vari-ation within than among populations (Kissing Kucek et al, 2019;Wiering et al, 2018). With an outcrossing reproductive system and open-pollination, any pedigree-based analysis is limited to maternal half-sib families with uncertain paternity.…”
Section: Reflection On Statistical Approachmentioning
confidence: 99%
“…For new breeding programs aimed at improving legume green manures (Kissing Kucek et al., 2019; Kissing Kucek, Riday, et al., 2020; Moore et al., 2020), farmers identified symbiotic N fixation (SNF) as the most important trait of interest (Wayman et al., 2017). So far, new breeding programs for legume green manures have focused on removing undesirable traits like seed dormancy (Kissing Kucek, Azevedo, et al., 2020) and improving cover crop establishment, overwinter survival, and spring biomass production (Kissing Kucek et al., 2019; Wiering et al., 2018). Breeding for SNF is more complicated because the goals and strategies may differ depending on the crop species, its agronomic functions, and the environments where it is grown.…”
Section: Introductionmentioning
confidence: 99%
“…Hairy vetch has exhibited high tolerance to winter stress (Brandsæter et al, 2008; Wiering et al, 2018) and high biomass production (Blevins et al, 1990; Teasdale et al, 2004), equating to greater fixed N 2 potential. Breeding efforts are ongoing to improve both the winter survivability and biomass yield of hairy vetch, an outcrossing species, for cover cropping in the midwestern United States (Wiering et al, 2018). Plant breeders have traditionally relied on visual approximations to phenotype biomass in vivo (Casler and van Santen, 2010) because it is nondestructive and generally time efficient.…”
mentioning
confidence: 99%
“…Winter annual legume cover crops, such as hairy vetch, provide soil coverage to stabilize the topsoil and provide biologically fixed N 2 for use by subsequent crops in a rotation (Herridge and Rose, 2000). Hairy vetch has exhibited high tolerance to winter stress (Brandsæter et al, 2008; Wiering et al, 2018) and high biomass production (Blevins et al, 1990; Teasdale et al, 2004), equating to greater fixed N 2 potential. Breeding efforts are ongoing to improve both the winter survivability and biomass yield of hairy vetch, an outcrossing species, for cover cropping in the midwestern United States (Wiering et al, 2018).…”
mentioning
confidence: 99%